Advances in the etiopathogenesis of vitiligo - Thomas Mathew; Sachin Vaidya (Pigment International)
Vitiligo is a disorder that causes depigmentation of the skin and can impact an individual’s quality of life, especially in those with darker skin types due to the contrasting nature. Over the last 30 years, a rise in vitiligo focused research has been observed. Its etiopathogenesis has been described as a complex interaction of various entities encompassing genetics, its downstream effects on the immune system, and subsequently interactions that it holds in conjunction with both exogenous and endogenous oxidative stressors. This review article aims to describe advancements in the etiopathogenesis of vitiligo with a focus on areas with growing evidence.